Observation about parasitism of Neodusmetia sangwani on rhodesgrass scale (Antonina graminis) - Filho, Antonio Batista; Silva, E. M. da (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out to determine the parasitism index of Neodusmetia sangwani (Rao, 1957) on the rhodesgrass scale (Antonina graminis Maskell, 1897). Adults of A. gramini infesting Rhynchelyhum repens (Wild) Hubb. field in Campinas, state of São Paulo, Brazil, were collected and taken to the laboratory. The insects were maintained inside glass containers, in a total of 75. This study was conducted at a temperature of 28oC and relative humidity of 65%. The results showed 35% of rhodesgrass attacked by N. sangwani. The number of female parasites was higher than of male. The average of parasitism was five hymenopteras for rhodesgrass. Only two parasites were not of the N. sangwani specie.